Recurrence of periodontitis and associated factors in previously treated periodontitis patients without maintenance follow-up - Fazele Atarbashi-Moghadam; Mohammadreza Talebi; Farnaz Mohammadi; Soran Sijanivandi (Tabriz University of Medical Sciences, 2020)
Background. Preventive dentistry, including supportive periodontal therapy (SPT), is one of the most critical areas of attention. Despite SPT's importance in the long-term success of periodontal treatment, the patients' adherence to it is weak. The present study aimed to evaluate of periodontal disease's recurrence rate and its related factors in periodontal patients without regular follow-up. Methods. A cross-sectional study was set in a specialized periodontics clinic in Tehran, Iran. Patients with periodontitis who completed periodontal therapy during 2005-2014 and did not adhere to the maintenance phase were evaluated. The periodontal history of the patients was updated. The previous diagnoses of patients according to their previous periodontal charts were revised by AAP 2015 criteria. Then, periodontal parameters were assessed, and current periodontal status was evaluated. Statistical analyses consisted of Fisher's exact test, t-test, Man-Whitney test, and Kruskal-Wallis test. Spearman's correlation coefficient was used to assess the relationship between factors and variables. Results. Fifty patients were evaluated, including 29 males and 21 females. There was a significant relationship between the initial diagnosis and recurrence rate of periodontitis (P=0.017). There was also a significant relationship between the recurrence of periodontitis and the years elapsed since the initial treatment (P=0.027, r = 0.353). Smoking significantly affected tooth loss (P=0.001). Conclusion. Patients with severe periodontitis need more attention to participate in supportive periodontal care. The patients must be aware of the disadvantages of neglecting this phase and be reminded of regular follow-up.